Hypothalamic and Metabolic Dysfunction in Genetic Models of Huntington’s Disease - Soylu Kucharz, Rana (Lund University: Faculty of Medicine, 2016)
Huntington’s disease (HD) is caused by a CAG trinucleotide repeat expansion in the huntingtin (HTT) gene. HD is an inherited progressive neurodegenerative disorder manifested by the wide array of motor dysfunctions, as well as non-motor symptoms. The latter include metabolic dysfunction and psychiatric deficits, such as depression and anxiety, are often observed in patients and animal models of HD and may precede motor symptoms by many years. Although recent evidence suggests that early non-motor symptoms may be caused by detrimental changes in the hypothalamus, a key brain region involved in modulating metabolism and emotions, the direct contribution of hypothalamic dysfunction to the development of the HD phenotype was never addressed in detail. This prompted us to explore the effects of mutant HTT expression in the hypothalamus and the cellular and molecular mechanisms involved in the development of non-motor symptoms. We show that the conditional BACHD mouse model of HD exhibit the obese phenotype with impaired glucose metabolism and leptin resistance, and the phenotype can be rescued by the inactivation of mutant HTT selectively in the hypothalamus with viral vector-mediated delivery of Cre recombinase. In reverse-design experiments, we demonstrate that viral vector-mediated expression of mutant HTT fragment locally in the hypothalamus is sufficient to recapitulate the metabolic dysfunction (Paper I). Furthermore, we suggest that the effects of HD hypothalamic dysfunction may be sex-specific and we imply the importance of specific cell populations to the development and progression of the disease. The paraventricular nucleus (PVN) is an important region of the hypothalamus in which patients and HD animal models exhibit cell loss and reduction in neuropeptide expression. As single-minded 1 (Sim1) transcription factor is a widely expressed in the PVN, we conditionally inactivated mutant HTT expression in Sim1 expressing cells of BACHD mice using a cross-breeding strategy. We show that the metabolic and depressive like phenotype have trends towards a rescue effect in male BACHD mice. In addition, we demonstrate that the hypothalamicpituitary- gonadal axis is altered in male BACHD mice with a reduced number of gonadotropin-releasing hormone expressing cells in the anterior hypothalamic area along with increased testes weight (Paper II). Lastly, we reveal the long-term effects of hypothalamic overexpression of mutant or wild-type form of HTT. We found that viral vector-mediated expression of both form of the HTT leads to metabolic dysfunction at 1 year post-injection, with the speed of progression of metabolic dysfunction correlating with the length of polyQ repeats. In addition, our data demonstrates that the selective expression of mutant HTT in the hypothalamus has detrimental effects on brown adipose tissue function and in turn energy balance by disrupting the hypothalamic dopaminergic pathway involved in thermogenesis (Paper III). Taken together, we provide the evidence for a causal link between mutant HTT expression in the hypothalamus and the metabolic dysfunction in HD. These findings represent a significant contribution to understanding HD pathology, rendering the hypothalamus as an attractive target for developing new treatment strategies for the disease.
ISSN: 1652-8220 Lund University, Faculty of Medicine Doctoral Dissertation Series 2016:8
Keywords: Huntington’s Disease; Huntingtin; Hypothalamus; Metabolism; Obesity; orexin; PVN; BAT; TH; neuroendocrinology